Analysis of Visual Representation of the Character in the Animated Film Jumbo - Gabriela Krisanti (Faculty Of Arts and Design Sebelas Maret University, 2026)
The development of a child's character is influenced not only by family and society but also by the media they consume. As one of the most popular Indonesian animated films this year, reaching 10 million viewers, Jumbo serves as a significant cultural reference. This research aims to explain the visual representation of Indonesian children through the film's characters and to identify the social values conveyed within the narrative. This study employs a qualitative descriptive method. To achieve a deep understanding of the visual and narrative layers, the researcher utilizes Roland Barthes’ Semiotics to deconstruct the denotative, connotative, and mythical meanings of the character designs. Furthermore, Stuart Hall’s Theory of Representation is applied to examine how these characters reflect the social identity and cultural reality of Indonesian children. The findings reveal that the visual design of each character meticulously represents the physical and stylistic reality of Indonesian children, specifically evoking the nostalgia and characteristics of the 2000s era. Beyond aesthetics, the storytelling in Jumbo serves as a vehicle for essential social values. The analysis identifies key themes such as solidarity, loyalty, empathy, tolerance, cooperation, and mutual assistance (gotong royong). Jumbo is not merely entertainment but a cultural artifact that mirrors the social attitudes and visual identity of Indonesian children, providing a relatable and value-driven viewing experience that contributes to character building.